2019
DOI: 10.1002/eahr.500028
|View full text |Cite
|
Sign up to set email alerts
|

Improving Translation and Cultural Appropriateness of Spanish‐Language Consent Materials for Biobanks

Abstract: A growing proportion of prospective research participants in the United States speak limited or no English. We conducted cognitive interviews with native Spanish speakers to test Spanish‐language translations of simplified and traditional biobank consent forms. Comprehension was generally high and did not differ by form. Most of those who received the simplified form felt it contained the right amount of information, compared with fewer than half of those who received the traditional form. Qualitative results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…As we uncover the role of language on enrollment, we recognize that studies have highlighted difficulties in research informed consent, when language barriers exist. 16-18 While we observed exclusion in studies based on preferred language, this may be more clearly explained as exclusion based on challenges in translating study materials into non-English languages and gaps in resources to devote to professional interpreter use in study visits. The ability to translate into plain English the implications and requirements of a research study is one which oncologists practice daily.…”
Section: Discussionmentioning
confidence: 74%
“…As we uncover the role of language on enrollment, we recognize that studies have highlighted difficulties in research informed consent, when language barriers exist. 16-18 While we observed exclusion in studies based on preferred language, this may be more clearly explained as exclusion based on challenges in translating study materials into non-English languages and gaps in resources to devote to professional interpreter use in study visits. The ability to translate into plain English the implications and requirements of a research study is one which oncologists practice daily.…”
Section: Discussionmentioning
confidence: 74%
“…Language is not only a barrier for biobanks and other health-related entities that share data and information, but also leads to inadequate understandings from patients or donors. [39] Alongside religious influence, cultural background, false patient perceptions about research procedures, and potential family influence, many individuals refuse to participate in clinical trials and/or donate biospecimens and related data. [40][41][42] According to poll participants and their personal experiences, cultural background, friends, family, and lack of trust in related procedures were all significant factors contributing to patients' or donors' final decision-making for donation and participation in research activities, emphasizing more on friends and family influence and/or the lack of trust in such procedures, regardless of the cultural background.…”
Section: Discussionmentioning
confidence: 99%
“…Das et al (2014) and Brelsford et al (2019) found slightly higher consent rates for the longer text version, whereas Edwards & Briddle (in press) found slightly higher consent rates for the shorter version. In the study of Brelsford et al (2019), more respondents felt the short or simplified form contained the right amount of information compared to the traditional form. The differences between the long and short versions are, however, not significant (or not tested (Brelsford et al, 2019)) in these studies.…”
Section: Text Lengthmentioning
confidence: 93%
“…Three studies experimented with the length of the consent text, a short version and a long version (Brelsford et al, 2019;Das et al, 2014;Edwards & Briddle, in press). Das et al (2014) and Brelsford et al (2019) found slightly higher consent rates for the longer text version, whereas Edwards & Briddle (in press) found slightly higher consent rates for the shorter version. In the study of Brelsford et al (2019), more respondents felt the short or simplified form contained the right amount of information compared to the traditional form.…”
Section: Text Lengthmentioning
confidence: 99%
See 1 more Smart Citation